Food and agriculture industries - Koppenhaver, Rebecca; Weisman, David; Stanford, Aaron; Intelecom (United State: Intelecom)
Surveys agriculture water issues, sugar cane and citrus processing in the Everglades, and featuresd dairy farms and cheese making. Concludes with a case study high-lighting reduced packaging wastes at McDonalds
Executive producer, Sally V. Beaty ; director of photography, Todd Pike
Narrated by Randy Oglesby
Keywords: Water in agriculture -- Management; Water-supply, Agricultural -- Management